PENGARUH PERBANDINGAN BUBUK KULIT ARI BIJI KAKAO : EKSTRAK KULIT BUAH JERUK NIPIS DAN WAKTU PENGADUKAN TERHADAP KARAKTERISTIK BODI KRIM - Putri Utami, I Gusti Ayu Agung; Ganda Putra, G. P.; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 1 (2019): MaretDO - 10.24843/JRMA.2019.v07.i01.p05, 2019)
Cream is a cosmetics in the form of a half-solid emulsion. This study aims to determine the effect of the comparison of the bark powder of the cocoa beans : extract of lime peel and the stirring time on the characteristics of body cream, determine the comparison of the bark powder of the cocoa beans : extract of lime peel and the stirring time that is best to produce body cream. This study uses factorial completely randomized design with 2 factors. The first factor is the comparison of the bark powder of the cocoa beans : extract of lime peel. The second factor is the stirring time of the body cream. The variables observed were material moisture content, pH, viscosity, dispersion, separation ratio, antioxidant capacity and color intensity. The results showed that the comparative treatment of the addition of the bark powder of cocoa beans and lime peel extract had a very significant effect on pH, dispersion, antioxidant capacity, brightness level (L*), redness level (a*), and yellowish level (b*) cream. The stirring time treatment has a significant effect on the brightness level (L *) of the cream. Comparative treatment of adding the bark powder of cocoa beans and extracts of lime peel, stirring time and interaction between the two treatments has a very significant effect on the viscosity of the cream. The comparison of the addition of the bark powder of cocoa beans : lime peel extract are 7.14: 7.14 grams and 15 minutes of stirring time was the best treatment, which can produce body cream with characteristic of pH 6,35, dispersion level 6,10 cm, viscosity 28.100 cp, separation ratio = 1, antioxidant capacity 125, 33 mg GAEAC/L, brightness level (L*) 43,78, redness level (a*)  6,73 and yellowish level (b*) 10,56. Keywords : body cream , addition of ingredients , and stirring time .